Inhibitory effects of a selective prostaglandin E2 receptor antagonist RQ-15986 on inflammation-related colon tumorigenesis in APC-mutant rats. - Yohei Shirakami (Public Library of Science (PLoS), 2021)
Prostaglandin E2 receptor EP4 is involved in inflammation and related tumorigenesis in the colorectum. This study aimed to investigate the chemopreventive ability of RQ-15986, a selective EP4 antagonist, in colitis-related colorectal tumorigenesis. Male Kyoto APC delta rats, which have APC mutations, were treated with azoxymethane and dextran sulfate sodium and subsequently administered RQ-15986 for eight weeks. At the end of the experiment, the development of colorectal tumor was significantly inhibited in the RQ-15986-treated group. The cell proliferation of the crypts and tumors in the colorectum was decreased following RQ-15986 treatment. RQ-15986 also suppressed the expression of pro-inflammatory cytokines, including tumor necrosis factor-α, interleukin-6, interleukin-18, and monocyte chemotactic protein-1, in the colon mucosa. In addition, the expression levels of indoleamine 2,3-dioxygenase, which is involved in immune tolerance, were decreased in the colorectal epithelium and tumors of the RQ-15986-treated group. These findings indicate that RQ-15986 inhibits colitis-associated colorectal tumorigenesis by attenuating inflammation, suppressing cell proliferation, and modulating the expression of indoleamine 2,3-dioxygenase. Targeting prostaglandin E2/EP4 signaling might be a useful strategy for chemoprevention of inflammation-related colorectal cancer.